2014
DOI: 10.1371/journal.pcbi.1003470
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Pathway of Interleukin 1 (IL-1) Initiated Signaling Reveals Mechanisms of Oncogenic Mutations and SNPs in Inflammation and Cancer

Abstract: Interleukin-1 (IL-1) is a large cytokine family closely related to innate immunity and inflammation. IL-1 proteins are key players in signaling pathways such as apoptosis, TLR, MAPK, NLR and NF-κB. The IL-1 pathway is also associated with cancer, and chronic inflammation increases the risk of tumor development via oncogenic mutations. Here we illustrate that the structures of interfaces between proteins in this pathway bearing the mutations may reveal how. Proteins are frequently regulated via their interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 63 publications
1
61
0
Order By: Relevance
“…It has been well documented that the propagation of IL-1␤ signaling mainly depends on MAPKs and their downstream effectors, which activate multiple transcription factors (22,23). Several reports have suggested that C/EBP is activated by IL-1␤ stimulation (16)(17)(18)(19)(20)(21); however, the underlying mechanism has not been fully described.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been well documented that the propagation of IL-1␤ signaling mainly depends on MAPKs and their downstream effectors, which activate multiple transcription factors (22,23). Several reports have suggested that C/EBP is activated by IL-1␤ stimulation (16)(17)(18)(19)(20)(21); however, the underlying mechanism has not been fully described.…”
Section: Discussionmentioning
confidence: 99%
“…Because several studies showed that TAK1 is an upstream regulator of NLK (2,3,5,37,42,43) and a downstream effector of IL-1␤-triggered signaling (22,23,(44)(45)(46), we examined the roles of TAK1 in ATF5 stabilization and C/EBP activation. In accordance with the results of the NLK experiments, overexpression of TAK1 activated C/EBP in cooperation with ATF5 in HEK293T cells (Fig.…”
Section: Nlk Activates the C/ebp Pathwaymentioning
confidence: 99%
See 3 more Smart Citations